Building Financial Management Capacity in Fragile and Confliict-Affected States : The Case of Liberia - World Bank (World Bank, Washington, DC, 2019)
This paper examines Liberia's financial management (FM) capacity building initiatives from the immediate aftermath of the 14-year civil war to date, and the lessons that could be drawn from such experiences for future efforts in the country and others faced with similar circumstances. The paper focuses on the merits and shortcomings of both donor supported and country-led initiatives that had FM skills development as a central theme.